ARTIFICIAL INTELLIGENCE AND TRANSLATION (TAMADDUN NURI JURNALI, 2024)
The article discusses the use of innovative technologies in the work of translators, citing their advantages and disadvantages. An assessment is made of the use of machine translation and artificial intelligence in oral and written translation. The author comes to the conclusion that existing machine translation systems are not yet able to compete with human translators. However, it is still difficult to predict when artificial intelligence will be able to fully perform the work instead of professional translators.